The Estrangement of Personhood as Guidance for the Community - Giampieri , Gabriele (E|C, 2024)
By comparing analyses from developmental psychology and anthropology studies is possible to detect how cultural interpretations of the infants’ intentions and skills radically influence the modes of attunement by which caregivers co-regulate their interactions with them. In turn, the different modes of attunement expressed in different cultural communities defer and transfer a particular idea of personhood. The following study intends to bring out the high pedagogical degree of cross-cultural analysis of the concept of person, how the resulting estrangement allows for the suspension of the identity relationship between person and selfhood, a necessary preamble to a collective and trans-individual revolution. The paper highlights how comparative methodology can enlighten a community regarding the structural incompleteness of any interpretation of personhood and guide its future pedagogies by overcoming the identity-alterity dichotomy.